Microstructural and tribological characterization of NiAl matrix self-lubricating composite coatings by atmospheric plasma spraying. (May 2017) - Li, Bo; Jia, Junhong; Gao, Yimin; Han, Minmin; Wang, Wenzhen
Abstract: The NiAl-Mo-Ag and NiAl-Cr2 O3 -Mo-Ag composite coatings were fabricated by atmospheric plasma spraying with the substrate material of Inconel 718. The effect of heat treatment on the microstructure, adhesive strength, microhardness and tribological properties of NiAl-Cr2 O3 -Mo-Ag composite coating was investigated. The heat treatment temperatures were chosen as 400, 500 and 600 °C. The composition and microstructure of composite coatings were analyzed by X-ray diffraction (XRD), scanning election microscopy (SEM) and transmission electron microscopy (TEM). The results show that the addition of Cr2 O3 could effectively reduce the wear rate of NiAl-Mo-Ag composite coating. The adhesive strength, microhardness and tribological properties of NiAl-Cr2 O3 -Mo-Ag composite coating were improved by heat treatment. After 500 °C heat treatment, the microstructure of composite coating became more homogeneous and the coating had the highest adhesive strength, microhardness and the best tribological properties. The sliding process could promote the silver, nickel and molybdenum occur tribo-chemical reaction to form silver molybdates and nickel molybdates lubricating films which were responsible for the good tribological properties of composite coatings at elevated temperatures. Highlights: Addition of Cr2 O3 could effectively reduce the wear rate of NiAl-Mo-Ag composite coating. Heat treatment could effectively improve the microhardness, adhesive strength and tribological properties of composite coating. The microstructure of the composite coating became more homogeneous after heat treated at 500 °C. The coating shown the highest hardness and adhesive strength and the best tribological properties after 500 °C heat treatment.